The Relation Between Banks' Funding Costs, Retail Rates and Loan Volumes: An Analysis of Norwegian Bank Micro Data - Arvid Raknerud; Bjørn Helge Vatne (Norges Bank, 2012)
We use a dynamic factor model and a detailed panel data set for six Norwegian bank groups to analyze i) how funding costs affect retail loan rates and ii) how retail rate differences between banks affect market shares. The data set consist of quarterly data for 2002Q1-2011Q3 and include information on loan volumes and retail (interest) rates for loans to firms and households. The cost of market funding is represented in our analysis by the three-month money market rate and a proxy for market risk the credit spread on unsecured senior bonds issued by Norwegian banks. Our estimates clearly suggest incomplete pass-through: a 10 basis points increase in the market rate leads to an approximately 8 basis points increase in retail loan rates. We also find that credit demand from households is more elastic with regard to the loan rate than demand from businesses.
hdl:11250/2496809
Keywords: C33; E27; E43; 330; monopolistic competition; credit spread; pass-through; funding costs; bank micro data; dynamic factor model